State of the art baby strollers: Design review and the innovations of an ergonomic baby stroller. Issue 1 (1st January 2017) - Sehat, A.R.; Nirmal, Umar
Abstract: The current work is an attempt to design and fabricate an ergonomic baby stroller with the latest state of the art features. A review on the design of baby strollers in the previous years was done ranging from the year 1980 to 2014. Based on the review it was found out that the idea of a foldable frame emerged since the early 1980s where people started to prioritize space saving. The use of electronics devices in strollers has not been properly implemented due to the bulkiness of the battery and the clutter mess of wires. Infant's safety and comfort has always been the number one priority by designing a seat that is contoured to a baby's spine, ultimately making baby's growth much safer. In lieu of the current work, a harmonious prototype design was fabricated using Rapid Prototyping system. The idea was to fuse the usage of electronics with the stroller by inventing modular "plug and play" attachment devices that provide customizability to baby strollers which include headlights and cooling fan attachments. Besides that, the latest state of the art designs of the ergonomic baby stroller such as a ventilated back rest, on-board rocking baby chair, bidirectional push handle with ergonomic grip support, frame with integrated hooks for storing different types of "plug and play" attachments and hooks for attaching the foldable stroller to a typical standard shopping cart were implemented.